Strategi Pembelajaran Berdiferensiasi dalam Materi Perubahan Wujud Zat pada Peserta Didik dengan Disabilitas Intelektual - Kusuna, Distiani Fitria (Jurnal Didaktika Pendidikan Dasar, 2025)
This research aims to see the effectiveness of differentiation learning strategies in science subjects for students with special needs. This research uses quantitative comparison with pre-test and post-test as a data collection design. The subjects of this research are 7 students with special needs, who have an IQ range of 50 - 80, or the equivalent of students who have intellectual disabilities. The pre-test and post-test data obtained were processed using the SPSS Wilcoxon-Rank Test and produced sig. .016 or sig <.05. These results show the effectiveness of differentiation learning strategies for students with special needs and intellectual disabilities in science subjects. In this research, it was also found that differentiated learning strategies were also able to improve the critical thinking abilities of students with intellectual disabilities. Where differentiation learning strategies are able to improve and bridge differences in the understanding abilities of each student with intellectual disabilities.